Testing Overreaction and Under-reaction in the Commodity Futures Market - DAI, Jingyu (Institutional Knowledge at Singapore Management University, 2012)
Results from previous studies testing for under-reaction and overreaction in the commodity futures market are mixed and inconclusive. Using a data of more than 20 categories of future contacts ranging from agricultural, metal and energy, we have found significant evidence of under-reaction in food and agricultural commodities but not in the energy and metal sector. It is also found that those relatively inactive commodity future contracts tend to have a stronger tendency to under-react than commodity future contracts are very actively traded. The result also agrees with the behavioral hypothesis that under-reaction is caused by gradual incorporation of information among investors.